Optimization of endodontic treatment methods. Choice of irrigation fluids (Эндодонтия Today, 2020)
Bacteria have been implicated in the pathogenesis and progression of pupal and periapical diseases. The primary aim of endodontic treatment is to remove as many bacteria as possible from root canal system and then create an environment in which remaining microorganisms cannot survive. Drugs form an important part of routine endodontic practice. They can been used in a number of ways: systemically, locally and prophylactically. One of them are antioxidants, they have been used as an root canal irrigant. This paper reviews the role of antioxidant «Acizol» in endodontics by highlighting its effects in detail.